The wild [videorecording (DVD)] - Belushi, James, 1954-; Buena Vista Home Entertainment (Firm); Garofalo, Janeane; Izzard, Eddie; Shatner, William; Silvestri, Alan; Sutherland, Kiefer, 1967-; Walt Disney Home Entertainment (Firm); Williams, Steven, 1949- (Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
Sampson is a lion on display at a zoo in New York City's Central Park, and he holds court over all the other animals, including Nigel, a testy koala bear; Larry, a dumb but well-meaning snake; Kazar, a wildebeest with a passion for choreography; Bridget, a bright but cynical giraffe; and Benny, a squirrel who is good friends with Sampson and is trying to romance Bridget without much success. Ryan is the pride and joy of Sampson's life and he becomes devastated when one day Ryan is crated up and sent away to another zoo. Sampson is desperate to find his boy, and with the help of his pals he escapes the zoo and sets out on a rescue mission. However, midtown Manhattan is unfamiliar territory for Sampson and the other zoo animals, and they have a hard time adjusting to the concrete canyons of the Big Apple.